2003
DOI: 10.1097/01.jom.0000052953.59271.e1
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Human Paraoxonase Gene Polymorphism and Chronic Symptoms in Pesticide-Exposed Workers

Abstract: Pesticides, such as parathion, are metabolized by cytochrome p-450 system to paraoxon, which is a potent cholinesterase inhibitor. Paraoxonase (PON) catalyzes the hydrolysis of these toxic metabolites and protects against pesticide toxicity. A glutamine/arginine (Gln/Arg) polymorphism at amino acid position 192 of PON has been described. The Arg/Arg genotype is associated with higher serum paraoxonase activity compared to Gln/Gln. The Arg/Gln genotype is associated with intermediate serum PON activity. The pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 11 publications
7
41
0
3
Order By: Relevance
“…In a study of Japanese farmers, exposure also occurred during spraying and pesticide poisoning led to acute dermatitis (5%) and chemical burns (3%) [25]. Lee, London, Paulauskis et al's study showed that working as a pesticide applicator was a predictor of chronic toxicity that included abdominal pain, nausea, rhinorrhea, dizziness, headache, somnolence, fatigue, gait isturbance, limb numbness, paresthesias, limb pain and limb weakness [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of Japanese farmers, exposure also occurred during spraying and pesticide poisoning led to acute dermatitis (5%) and chemical burns (3%) [25]. Lee, London, Paulauskis et al's study showed that working as a pesticide applicator was a predictor of chronic toxicity that included abdominal pain, nausea, rhinorrhea, dizziness, headache, somnolence, fatigue, gait isturbance, limb numbness, paresthesias, limb pain and limb weakness [22].…”
Section: Discussionmentioning
confidence: 99%
“…Other research showed a link between pesticide exposure and adverse effects on children and fetuses such as low birth weight [17,18], preterm birth or toxemia [19], stillborn infants [20] and miscarriages [21]. In China's Anhui province, DDT was associated with miscarriages in the first few weeks of pregnancy [22]. In Ecuador, women exposed to pesticides in the cut-flower industry were at risk of spontaneous abortion [23].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the PON1 192R alloform hydrolyzes paraoxon in vitro with greater catalytic efficiency than does the PON1 192Q alloform, whereas the PON1 192 alloforms hydrolyze diazinon oxon (diazoxon) with nearly equivalent catalytic efficiencies (Haley et al, 1999;Furlong et al, 2000b;Lee et al, 2003). In each example, the PON1 192QR genotype shows an intermediate activity relative to the PON1 192RR and PON1 192QQ alloforms.…”
Section: Introductionmentioning
confidence: 99%
“…This finding was likely because non-applicators are still exposed to OP pesticides through other indirect means. Interestingly, in this study, neither RBC nor plasma cholinesterase levels were statistically significant predictors of chronic cholinergic toxicity [13].…”
Section: Op Compound Metabolism and Toxicitymentioning
confidence: 84%